About the dispositif and the filmic dispositif - Ferreira, Alana de Oliveira (Revista do Colóquio, 2022)
This article explores the relationship between the concept of “dispositif” and its applications in cinema and photography, with an emphasis on the critique of realism and objectivity in these media. The term, originally proposed by Michel Foucault and expanded by Giorgio Agamben, is described as a set of practices and mechanisms of social control that shape behaviors and discourses. In cinema, Jean-Louis Baudry and Philippe Dubois highlight how the cinematic “dispositif” imposes a passive experience on the spectator, naturalizing the illusion of reality and questioning the ideological value of images. Hubert Damisch and Pierre Bourdieu argue that the photographic apparatus is not neutral, but a cultural construction that reinforces conventions of visual representation. It is concluded that, despite such characteristics of the device, video art works allow for active participation by the viewer, who moves from being a mere observer to an agent who interacts with the space and the images, stimulating reflections on the relationship between image, power and reality.